Legal Protection for Consumers Against Subsidized LPG Gas Sales that Exceed the Highest Retail Price (HET) in Samarinda City: PELINDUNGAN HUKUM BAGI KONSUMEN TERHADAP PENJUALAN GAS LPG BERSUBSIDI YANG MELEBIHI HARGA ECERAN TERTINGGI (HET) DI KOTA SAMARINDA - Meli Setianur; Surahman (Program Studi Magister Ilmu Hukum Universitas Islam Nusantara, 2025)
This study aims to analyze legal protection for consumers against the practice of selling subsidized LPG that exceeds the Highest Retail Price (HET) in Samarinda City. The study uses an empirical legal method with data obtained through interviews, observations, and questionnaires to the community, business actors, and related agencies. By using qualitative analysis, the data that has been obtained will then draw conclusions from this problem. The results of the study indicate that there are violations of HET that have an impact on consumers, especially from low-income groups. Although it has been regulated through the Decree of the Governor of East Kalimantan Number 500/K.572/2022 and Law Number 8 of 1999 concerning Consumer Protection (UUPK), its implementation has not been effective. The obstacles faced include weak supervision, lack of human resources for supervisors, lack of public awareness of consumer rights, and legal loopholes in LPG distribution regulations. This study suggests the need to strengthen supervision, educate the public, and revise regulations to ensure that consumer protection can be realized optimally.